Analysis of impact in implemented strategies to help improve in the learning of Mathematics for students who go into the first semester - Uzuriaga Lopez, Vivian Libeth; Mejia, Diana Paola (Scientia et Technica, 2019)
This research aims to establish the influence on academic performance, and perform some measurement and diagnosis processes which generate accurate knowledge of the conditions surrounding the student population in terms of their level of competence development upon arrival at the institution. Among these measurement elements is found the Diagnostic Test in Mathematics, whose purpose is to delve right into the competences of the students in the handling of numbers, their operations, and their application towards the solution of problems. These results which have been obtained from the study are socialized between the relation of the diagnostic test in mathematics and the academic performance population out of students that went firstly into the Engineering and Technology Faculties from the Technological University Pereira in the first semester of 2017, moreover, it is analyzed some strategies used to do better in the shortcomings of learning which are linked to the Academic Accompaniment Program.